Canga biodiversity, a matter of mining - Skirycz, Aleksandra; Castilho, Alexandre; Chaparro, Cristian; Carvalho, Nelson; Tzotzos, George; Siqueira, Jose O. (Frontiers in Plant Science, 2014)
Brazilian name canga refers to the ecosystem associated with superficial iron crusts typical for the Brazilian state of Minas Gerais (MG) and some parts of Amazon (Flona de Carajas). Iron stone is associated with mountain plateaux and so, in addition to high metal concentrations (particularly iron and manganese), canga ecosystems, as other rock outcrops, are characterized by isolation and environmental harshness. Canga inselbergs, all together, occupy no more than 200km2 of area spread over thousands of km2 of the Iron Quadrangle (MG) and the Flona de Carajas, resulting in considerable beta biodiversity. Moreover, the presence of different microhabitats within the iron crust is associated with high alpha biodiversity. Hundreds of angiosperm species have been reported so far across remote canga inselbergs and different micro-habitats. Among these are endemics such as the cactus Arthrocereus glaziovii and the medicinal plant Pilocarpus microphyllus. Canga is also home to iron and manganese metallophytes; species that evolved to tolerate high metal concentrations. These are particularly interesting to study metal homeostasis as both iron and manganese are essential plant micro-elements. Besides being models for metal metabolism, metallophytes can be used for bio-remediation of metal contaminated sites, and as such are considered among priority species for canga restoration. “Biodiversity mining” is not the only mining business attracted to canga. Open cast iron mining generates as much as 5-6% of Brazilian gross domestic product (GDP) and dialogue between mining companies, government, society and ecologists, enforced by legal regulation, is ongoing to find compromise for canga protection, and where mining is unavoidable for ecosystem restoration. Environmental factors that shaped canga vegetation, canga biodiversity , physiological mechanisms to play a role, and ways to protect and restore canga will be reviewed.